Alternative indicators of population ageing: An inventory - Jeroen Spijker (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2015)
The extent, speed and impact of population ageing have often been exaggerated because standard indicators such as the Old-Age Dependency Ratio or Support Ratio do not take proper account of falling mortality, the changing relationship between age and employment, or (usually) both. Neither do such ratios consider the changing composition in terms of educational attainment, human capital or other population characteristics. Not surprisingly, over the last decade or so demographers have developed alternatives. This paper provides an overview of such alternatives and briefly discusses their utility.
Keywords: 300; Ageing; dependency ratio; support ratio; alternative indicators of ageing; life expectancy; employment